2020
DOI: 10.1177/1362361320956876
|View full text |Cite
|
Sign up to set email alerts
|

‘I just rolled up my sleeves’: Mothers’ perspectives on raising girls on the autism spectrum

Abstract: Little previous research has elucidated the everyday experiences of autistic girls or their families. This study used qualitative in-depth interviews to explore mothers’ experiences of the diagnosis, presentation and impact of caring for a daughter with autism. Nineteen women with autistic daughters (aged between 7 and 18) participated in the research, which took place in Ireland. Thematic analysis identified six themes: What’s Going On?; Road to Acceptance; Beyond the Stigma of Autism; Autism: Like a Girl; Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 82 publications
(117 reference statements)
1
9
0
Order By: Relevance
“…Findings reported here could have important implications. Indeed, accessing interventions outside of the home is challenging for caregivers, requiring considerable free time (Fowler & O'Connor, 2021). The current intervention, quick to use and accessible from home, circumvents these practical barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Findings reported here could have important implications. Indeed, accessing interventions outside of the home is challenging for caregivers, requiring considerable free time (Fowler & O'Connor, 2021). The current intervention, quick to use and accessible from home, circumvents these practical barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of autistic children revealed that most were boys (72.6%) with higher ZBI scores in mothers of female children; also, there is a significant association of ZBI and PSS scores noted with the gender of the child. In an Irish study, Fowler and O'Connor [27] reported that parents of girls with ASD face a higher stress level along with social similar stigmatization is commonly seen in Pakistan and the brunt is born the mothers. In a local study, Sabih F. found that parents of female-child with ASD experience more stress than parents of male children [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on the experiences of mothers to autistic girls identify "unique challenges" due to "female specific social pressures" (Fowler and O'Connor 2020, p. 2), "scepticism" (Navot et al, 2017, p. 538), and diagnostic delay (Fowler andO'Connor 2020, Navot et al, 2017). Anderson et al, (2020) found that the mothers they interviewed had an "early sense of something being different" about their daughters but "most did not arrive at autism as the explanation for this difference" (p. 1549), again highlighting the important role of professionals in raising autism as a possibility.…”
Section: Autism and Girls -"Not Different Enough"mentioning
confidence: 99%
“…Navot et al, (2017) found that even after delays in receiving a diagnosis for their daughters, the mothers of autistic girls were twice excluded due to "a sense of exclusion from the neurotypical population and male dominant ASD population". However, studies have also highlighted many benefits to the diagnosis including the mother's pride in their daughters (Fowler and O'Connor 2020), an increase in empathy and understanding (Anderson et al, 2020), and a re-shaping of maternal competence and the creation of a "different bond" (Navot et al, 2017).…”
Section: Autism and Girls -"Not Different Enough"mentioning
confidence: 99%